Development of Natural and Artificial Ecosystem Diorama Learning Media (Simita) Ecosystem Theme for Class V Students - Anisa, Debli Dwi; Sofiyana, Marinda Sari; Sholihah, Mar'atus (Universitas Islam Balitar, 2024)
This research focuses on student responses and the feasibility of Simita diorama learning media on an ecosystem theme for class V students. With this focus, this research aims to develop Simita diorama media on an ecosystem theme for class V students. The research method used is Research and Development (R&D), because the research method is used to produce certain products and test the effectiveness of these products. The observation stage was carried out at three elementary schools in Blitar, namely MI Hidayatul Ulum, SDN Sanankulon 02, and SDN Karangsari 03. The Simita diorama learning media trial was carried out in the instructional simulation trial stage using 12 students to determine student responses to the Simita diorama learning media. as a participant in a limited trial. The results of the research show that the Simita diorama learning media on ecosystem theme material in class V elementary school has gone through a feasibility test by material expert validators, media experts and language experts. The percentage obtained from material expert validators was 81.3%, media expert validators 91.1%, and language expert validators 85%. Based on the validator results, it can be concluded that the Simita diorama learning media is categorized as appropriate by experts. Based on the analysis of questionnaire data, students' responses to the Simita diorama media obtained a percentage score of 95.8% with very good information